2010
DOI: 10.1080/01635580903532416
|View full text |Cite
|
Sign up to set email alerts
|

Lentinan: Hematopoietic, Immunological, and Efficacy Studies in a Syngeneic Model of Acute Myeloid Leukemia

Abstract: Lentinan, a beta-glucan nutritional supplement isolated from the shitake mushroom (Lentula edodes), is a biological response modifier with immunostimulatory properties. Concomitantly, the role of beta-glucans as chemoimmunotherapeutic in a number of solid cancers has been widely documented. We investigated the effects of nutritional grade lentinan upon BN rats and in a preclinical syngeneic model of acute myeloid leukemia. BN rats supplemented daily with lentinan exhibited weight gains, increased white blood c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 38 publications
2
22
0
Order By: Relevance
“…To further explore the VPA-resistance mechanisms we utilized the Brown Norwegian myeloid leukemia (BNML) syngeneic rat leukemia model which provides highly reproducible responses to conventional chemotherapeutics [18], [36] with the advantage of a complete host immune system during leukemia growth and therapy. We developed a progressive disease model in the BNML rats by giving animals suboptimal doses of VPA (170 mg/kg b.i.d.…”
Section: Resultsmentioning
confidence: 99%
“…To further explore the VPA-resistance mechanisms we utilized the Brown Norwegian myeloid leukemia (BNML) syngeneic rat leukemia model which provides highly reproducible responses to conventional chemotherapeutics [18], [36] with the advantage of a complete host immune system during leukemia growth and therapy. We developed a progressive disease model in the BNML rats by giving animals suboptimal doses of VPA (170 mg/kg b.i.d.…”
Section: Resultsmentioning
confidence: 99%
“…Preclinical data show good evidence for a beneficial effect of b-glucan in cancer [38][39][40]; however, there is some debate about whether these effects are due to direct cytotoxic effects or immunomodulatory mechanisms [41,42]. For example, Yoon et al reported that b-glucan purified from mutated S. cerevisiae inhibited lung metastasis of colon 26-M3.1 carcinoma that was associated with splenocyte proliferation, tumoricidal activity of peritoneal macrophages, and NK cell cytotoxicity but there was no effect of this treatment on direct cytotoxicty of colon 26-M3.1 cells in vitro [43].…”
Section: B-glucan and Cancermentioning
confidence: 99%
“…In particular, the potential role of medicinal mushrooms as adjuvant therapy for solid tumors and acute leukemia has been extensively investigated [12][13][14][15]. The edible Bacidiomycota mushroom Agaricus blazei Murill (AbM) grows naturally in an area near São Paulo, Brazil, where it has been used in traditional medicine against a variety of diseases, including infection and cancer [16].…”
Section: Introductionmentioning
confidence: 99%